Karakteristik Bubuk Penyedap Over-Fermented Tempeh Dengan Perlakuan Lama Fermentasi - Nirmalasari, Putu Linda Ratna; Indri Hapsari Arihantana, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Soybean tempeh is one of the original Indonesian foods that is best known and liked by the general public. Making soybean tempeh is done by fermenting soybeans with the help of fungi for 2 days. The longer the tempeh fermentation time will affect the physical and chemical quality of the tempeh. Tempeh in this condition is called over-fermented tempeh. Over-fermented tempeh can be used as an alternative flavoring due to its high amino acid content, especially glutamic acid. The fermentation time for tempeh is directly proportional to the levels of glutamate acids produced so it can produce an umami taste. The flavors contained in over-fermented tempeh can be developed into preparations such as cooking spices. The purpose of this research is to determine the optimal tempeh fermentation duration for producing flavoring powder with optimal features, as well as the impact of fermentation time on the properties of flavoring powder derived from over-fermented tempeh. In this study, lengthy fermentation treatments 48, 72, 96, 120, and 144 hours were utilized in a fully randomized design. To create 15 experimental units, the procedure was carried out three times. Variance analysis was used to assess the data, and the Duncan Multiple Range Test was used to determine if the therapy had a true impact. The study's findings demonstrated that while fermentation time had no discernible impact on the value of water content or the value of liking flavor and texture, it did have a substantial impact on the value of protein content, glutamic acid, color, scent, and overall acceptability. Over-fermented tempeh flavoring powder with the greatest qualities was created by a lengthy 144-hour fermentation process. Its water content was 6,15%; protein 41,73%; glutamic acid 73.58%, and its color, fragrance, taste, texture, and general acceptance were all rather positive. Keywords: fermentation time, flavored powder, over-fermented tempeh, tempeh